Rynek obligacji korporacyjnych w Polsce w obliczu zmian legislacyjnych. Przegląd kluczowych rozwiązań w ustawie z dn. 15 stycznia 2015 r o obligacjach - Bielawska, Aurelia; Pawłowski, Maciej (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article attempts to analyze and evaluate the changes in the legal environmentgoverning bond issuance in Poland. The analysis is focused on the contentand changes introduced by the new Act on Bonds of 15 January 2015. The highlightedissues are considered from the point of view of issuers and investors onthe corporate bond market.